your answer for this question is y=c hope this helps
Answer:
Yes youre answer is correct
Step-by-step explanation:
9514 1404 393
Answer:
3. vertical stretch by a factor of 2; shift right 1 and down 1
4. shift left 4 and up 4 (no stretch or shrink)
Step-by-step explanation:
The vertex form equation is ...
y = a(x -h)^2 +k
It represents a vertical stretch of the parent function by a factor of 'a', a right shift of 'h', and an upward shift of 'k'.
Compare the the given equations to the above form to see the transformations.
__
3. (a, h, k) = (2, 1, -1) ⇒ vertical stretch by a factor of 2; shift right 1, down 1
4. (a, h, k) = (1, -4, 4) ⇒ no vertical stretch; shift left 4, up 4
Answer:
12
Step-by-step explanation:
12x12 is 144
Since we know x=6, replace all the x with 6 in the equation and then follow the PEMDAS rule. y= -2(6)^2 + 2(6) + 2 y= -2 (36) + 2 (6) + 2 y= -72 + 12 + 2 y= -60+2 y= -58